Well-Being and Satisfaction of Nurses in Slovenian Hospitals: A Cross-Sectional Study - Lorber Mateja; Treven Sonja; Mumel Damijan (Sciendo, 2020)
Well-being is one of the most important factors in whether nurses decide to remain in the nursing profession. This study aims to examine well-being and satisfaction among nurses working in Slovenian hospitals and to identify the related demographic factors.